2019
DOI: 10.1111/jcmm.14523
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination of DT‐13 and Topotecan inhibits aerobic glycolysis in human gastric carcinoma BGC‐823 cells via NM IIA/EGFR/HK II axis

Abstract: DT‐13 combined with topotecan (TPT) showed stronger antitumour effects in mice subcutaneous xenograft model compared with their individual effects in our previous research. Here, we further observed the synergistically effect in mice orthotopic xenograft model. Metabolomics analysis showed DT‐13 combined with TPT alleviated metabolic disorders induced by tumour and synergistically inhibited the activity of the aerobic glycolysis‐related enzymes in vivo and in vitro. Mechanistic studies revealed that the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Based on these observations, we used HTS to evaluate the effect of 958 FDA-approved drugs and identify those capable to increase R77C-α-SG rescue without increasing BTZ-induced proteasome inhibition and its associated cell toxicity. In the past decade, similar strategies have already been reported to identify drugs increasing effects (Chumakov et al, 2014; Yu et al, 2019) or alleviating side effects (Hajj et al, 2015; Zhou et al, 2019) of other therapeutic agents. In this study, we identified 47 compounds all capable to increase R77C-α-SG rescue and belonging mostly to HSP90i, HDACi, aurora kinase inhibitors (AKi) and cyclin-dependent kinase inhibitors (CDKi) families.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we used HTS to evaluate the effect of 958 FDA-approved drugs and identify those capable to increase R77C-α-SG rescue without increasing BTZ-induced proteasome inhibition and its associated cell toxicity. In the past decade, similar strategies have already been reported to identify drugs increasing effects (Chumakov et al, 2014; Yu et al, 2019) or alleviating side effects (Hajj et al, 2015; Zhou et al, 2019) of other therapeutic agents. In this study, we identified 47 compounds all capable to increase R77C-α-SG rescue and belonging mostly to HSP90i, HDACi, aurora kinase inhibitors (AKi) and cyclin-dependent kinase inhibitors (CDKi) families.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of CSCC, glycolysis can provide energy and opportunities for the tumor cells to reproduce and invade [ 25 ]. Additionally, the enhancement of glucose metabolism in tumor cells is related to the activity of rate-limiting enzymes during glycolysis [ 37 , 38 ]. Here, PFKFB3 expression was also upregulated in CSCC cells, and PFKFB3 knockdown could suppress the aerobic glycolysis of A431 cells, thereby inhibiting the cell proliferation and impeding the development of CSCC.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been proved in vivo in BGC-823 xenograft mice with the dosage of DT-13 at 1.25 mg/kg/d combined Topotecan at 0.5 mg/kg/d. Mechanistic studies show that combination treatments promote the degradation of epidermal growth factor receptors through the activity of non-muscle myosin IIA, thus inhibiting HK2 activity, simultaneously suppressing the specific binding of HK2 to mitochondria, and attenuating aerobic glycolysis ( Yu et al, 2019 ).…”
Section: Phytochemicals Against Glycolysis In Gastric Cancer Cellsmentioning
confidence: 99%